Lack of clinical manifestations in asymptomatic dengue infection is attributed to broad down-regulation and selective up-regulation of host defence response genes - Yeo, A.S.L.; Azhar, N.A.; Yeow, W.; Talbot Jr, C.C.; Khan, M.A.; Shankar, E.M.; Rathakrishnan, A.; Azizan, A.; Wang, S.M.; Lee, S.K.; Manikam, R. (Public Library of Science, 2014)
Objectives Dengue represents one of the most serious life-threatening vector-borne infectious diseases that afflicts approximately 50 million people across the globe annually. Whilst symptomatic infections are frequently reported, asymptomatic dengue remains largely unnoticed. Therefore, we sought to investigate the immune correlates conferring protection to individuals that remain clinically asymptomatic. Methods We determined the levels of neutralizing antibodies (nAbs) and gene expression profiles of host immune factors in individuals with asymptomatic infections, and whose cognate household members showed symptoms consistent to clinical dengue infection. Results We observed broad down-regulation of host defense response (innate, adaptive and matrix metalloprotease) genes in asymptomatic individuals as against symptomatic patients, with selective up-regulation of distinct genes that have been associated with protection. Selected down-regulated genes include: TNF Î± (TNF), IL8, C1S, factor B (CFB), IL2, IL3, IL4, IL5, IL8, IL9, IL10 and IL13, CD80, CD28, and IL18, MMP8, MMP10, MMP12, MMP15, MMP16, and MMP24. Selected up-regulated genes include: RANTES (CCL5), MIP-1Î± (CCL3L1/CCL3L3), MIP-1Î² (CCL4L1), TGFÎ² (TGFB), and TIMP1. Conclusion Our findings highlight the potential association of certain host genes conferring protection against clinical dengue. These data are valuable to better explore the mysteries behind the hitherto poorly understood immunopathogenesis of subclinical dengue infection.